Correction: Feng et al. Photobiomodulation Inhibits Ischemia-Induced Brain Endothelial Senescence via Endothelial Nitric Oxide Synthase. Antioxidants 2024, 13, 633 - Yu Feng; Zhihai Huang; Xiaohui Ma; Xuemei Zong; Vesna Tesic; Baojin Ding; Celeste Yin-Chieh Wu; Reggie Hui-Chao Lee; Quanguang Zhang (MDPI AG, 2024)
In the original publication [...]